Preparation and evaluation of partially‐substituted 3‐chloro‐4‐methylphenylcarbamate‐β‐cyclodextrin bonded silica particles as chiral stationary phase for multi‐mode HPLC. Issue 1 (25th January 2019) - Meng, Min; Ma, Mingxuan; Yi, Jingxuan; Xu, Lu; Yin, Xiaoxing; Gu, Qinglong; Yin, Jiale; Du, Lei; Zhu, Xia; Zhou, Xueyan; Wei, Qunli; Gong, Yinhan
Abstract: 3‐Chloro‐4‐methylphenylcarbamate‐(3‐(2‐O‐β‐cyclodextrin)‐2‐hydroxypropoxy)‐propylsilyl‐appended silica particles (CMP‐CD‐HPS), a new type of partially‐substituted cyclodextrin‐bonded phase, have been successfully synthesized and applied as a chiral stationary phase in high‐performance liquid chromatography under multi‐mode conditions including normal phase, reversed phase, and polar organic mobile phase conditions. Chemical characterization for the CMP‐CD‐HPS was carried out by elemental analysis. The chromatographic performance of CMP‐CD‐HPS‐packed column was evaluated by separating the positional isomers of nitrophenol and nitraniline and the enantiomers of some chiral drug compounds. The separation results show that CMP‐CD‐HPS exhibited excellent selectivity for separating the positional isomers of disubstituted benzenes and the enantiomers of the chiral drugs. The hydroxyl residues of partially‐substituted β‐cyclodextrin and the stable spacer linking to secondary hydroxyl site of the β‐cyclodextrin in the new CMP‐CD‐HPS phase play important roles in the chromatographic separations.